Pelaksanaan Pemberian Asimilasi terhadap Warga Binaan Pemasyarakatan di Rumah Tahanan Negara Kelas IIB Padang Panjang - Abdi, Rezki Kurnia; Yustrisia, LoLa; Munandar, SyaifuL (Wajah Hukum, 2023)
AssimiLation is the process of fostering CorrectionaL Assisted Residents and CorrectionaL Students which is carried out by mixing CorrectionaL Assisted Residents and CorrectionaL Students in community Life. This study discusses the impLementation of the provision of assimiLation to prisoners in the Padang Panjang CLass IIB State Detention Center. The issues raised how is the impLementation of the granting of AssimiLation Rights to CorrectionaL Inmates in the Padang Panjang CLass IIB State Detention Center and what are the obstacLes and efforts in impLementing the granting of AssimiLation Rights to CorrectionaL Inmates in CLass IIB Padang Panjang State Detention Center. The type of research used is empiricaL juridicaL research. Sources of data used are primary data and secondary data. The impLementation of the granting of the Right of AssimiLation to CorrectionaL FamiLies in CLass IIB Padang Panjang State Detention Center is in accordance with appLicabLe reguLations. However, there are stiLL a number of obstacLes in the procedure which are stiLL not effective, there is resistance from the community towards prisoners and chiLdren of correctionaL institutions. It is better if there is more sociaLization from correctionaL officers to the inmates so that they are interested in fuLfiLLing their assimiLation rights. There is sociaLization that is more motivating from correctionaL officers to inmates so that they are interested in fuLfiLLing their assimiLation rights so that they avoid new criminaL acts when assimiLation is given.